Effect Of Low Frequency Excitation Location For Crack Detection In Aluminium Plate Using Nonlinear Vibro-Acoustic Method - Hermanto, Tino (2021)
Fatigue crack occurs due to the material failure to withstand the load when applied repeatedly. Nonlinear vibro-acoustic is a highly reliable and sensitive method for damage detection. Vibro-acoustics method (VAM) is a method based on the fact that a high frequency ultrasonic wave propagates in the testing structure is modulated by the low frequency excitation. Besides that, the interaction between a high frequency vibration and a low frequency vibration results in nonlinear acoustic wave modulation. Low frequency excitation is a crucial element of nonlinear acoustic technique when used for crack detection. It is important to know what frequencies and level of excitation required to fully open cracks and where to excite the structure in order to maximize the detectability of the crack. The purpose of this research are to determine the optimized excitation location and investigate the effect of the first three vibration mode shapes natural frequencies on crack detection in cracked aluminium Al-2024 plate specimen by using VAM techniques. Micro-crack was created on aluminium plate by using Electro Discharge Machine (EDM) and fatigue test. The plate was hung with cords to provide free boundary condition. A mechanical shaker by a TIRA GmbH type S 50018 is attached at bottom corner of the plate and suspended by soft string. The piezoelectric transducer were used to provide simultaneous interaction between low frequency excitation and high frequency inputs respectively. Three middle cracked plate were excited with first, second and third mode frequency excitation at excitations 21 positions for modal analysis. The experimental modal analysis carried out were validated by finite element model simulation. The surface deflection above the crack are measured by Optomet SWIR scanning laser Doppler vibrometer in time domain signal are converted into frequency signal by using MATLAB software. Surface deflections was used to determine the most effective frequency mode and excitation location. The amplitude modulation intensity, R-values were used to determine the effectiveness of the frequency to predict the crack location in the aluminium plate. The results show the surface deflection and R-value are highest at the bottom corner of the plate. These shows that the most effective locations for excitation is at the edge of plate (location 15) and first vibration mode frequency produces the most significant effect on crack detection. Thus the selection of vibration mode frequency and excitation location are important in nonlinear vibro-acoustic defect detection technique.